Evaluation of recent initial public offers subscription levels in the Nairobi Securities Exchange - Mulu, Mercy Kalyali (Strathmore University, 2014)
This study investigates the determinants of success for IPOs in the Nairobi Securities Exchange by making a comparative analysis of under - subscribed and oversubscribed IPOs. The population of the study consisted of all initial public offers of common stock at the NSE during the period 200 l-20 ll. Six out of nine of the recent IPOs in Nairobi Stock Exchange have been highly oversubscribed while the remaining three IPOs had subscription levels of 60%, 80% and 60% respectively. In light of these subscriptions, this study investigates why some of the IPOs in Kenya were oversubscribed while others were under - subscribed, what factors were at play to contribute to these subscriptions and finally what does a firm need to do in order to have a successful IPO in the local market. This was aided by the use of questionnaires to collect data from the respondents. Non- parametric methods (Sign Test and Wilcoxon methods) were used to analyze the data obtained which led to the findings that a strong customer base, company expertise, the age of the company, access to a wide capital base, research and development in growth opportunities and business bench - marking go hand in hand with the success of the companies going public.
Evaluation of recent initial public offers subscription levels in the Nairobi Securities Exchange
A research project submitted in partial fulfillment of the requirements for the award of Bachelor of Business Science Actuarial Science
Keywords: Public offers; Subscription levels; Nairobi Securities Exchange